Cross-Country Electricity Trade, Renewable Energy and European Transmission Infrastructure Policy - Jan Abrell; Sebastian Rausch (ETH Zurich, CER-ETH - Center of Economic Research, 2016)
This paper develops a multi-country multi-sector general equilibrium model, integrating high-frequency electricity dispatch and trade decisions, to study the e ects of electricity transmission infrastructure (TI) expansion and re- newable energy (RE) penetration in Europe for gains from trade and carbon dioxide emissions in the power sector. TI can bene t or degrade environ- mental outcomes, depending on RE penetration: it complements emissions abatement by mitigating dispatch problems associated with volatile and spa- tially dispersed RE but also promotes higher average generation from low- cost coal if RE production is too low. Against the backdrop of European decarbonization and planned TI expansion, we nd that emissions increase for current and targeted year-2020 levels of RE production and decrease for year-2030 targets. Enhanced TI yields sizeable gains from trade that de- pend positively on RE penetration, without creating large adverse impacts on regional equity.
Keywords: F18; Q28; Q43; Q48; C68; 330; Stromnetz; Erneuerbare Energie; Infrastrukturpolitik; Elektrizität; Außenhandel; Allgemeines Gleichgewicht; EU-Energiepolitik; EU-Umweltpolitik; Mehr-Länder-Modell; EU-Staaten